Faktor Yang Memengaruhi Struktur Modal Perusahaan Barang Konsumsi Tahun 2017-2019 - Nelson Kristianto, Merry Susanti (Jurnal Paradigma Akuntansi, 2021)
This study was designed to examine the effect of profitability, liquidity, tangibility, non-debt tax shield, growth, firm size and firm age on the capital structure of consumer goods companies in 2017-2019. This study used a purposive sampling method which resulted in a sample of 36 consumer goods companies listed in the Indonesia Stock Exchange in 2017-2019 with a total of 108 data for 3 years. This study used secondary data in the form of corporate financial reports which can be downloaded through the website www.idx.co.id and the official websites of the related companies. The data processing technique is performed using panel data regression assisted by the E-views 10 software application. The results showed that profitability and liquidity had a negative effect on capital structure, while firm size had a positive effect on capital structure. Tangibility, non-debt tax shield, growth and company age had no effect on capital structure. The implication of this research is that investors and managers need to pay attention to the company's profitability, liquidity and firm size because it can affect the condition of the capital structure in the company.